2020
DOI: 10.1186/s12929-019-0613-y
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor and GSK3β signaling mediate deficits in novel object recognition memory within dopamine transporter knockdown mice

Abstract: Background: Over-stimulation of dopamine signaling is thought to underlie the pathophysiology of a list of mental disorders, such as psychosis, mania and attention-deficit/hyperactivity disorder. These disorders are frequently associated with cognitive deficits in attention or learning and memory, suggesting that persistent activation of dopamine signaling may change neural plasticity to induce cognitive or emotional malfunction. Methods: Dopamine transporter knockdown (DAT-KD) mice were used to mimic a hyper-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It has been found that the deletion of D3R in DAT knockdown mice restores novelty-induced GSK3β activation in the medial PFC. Moreover, inhibition or knockdown of GSK3β, but not the α isozyme, in the medial PFC of wild-type mice impairs recognition memory [160], which suggests that in the medial PFC, D3R acts via GSK3β signaling to play a role in the novel objects recognition memory.…”
Section: Da and 5-ht/akt/gsk3 Pathway Modulation And Its Behavioral Cmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been found that the deletion of D3R in DAT knockdown mice restores novelty-induced GSK3β activation in the medial PFC. Moreover, inhibition or knockdown of GSK3β, but not the α isozyme, in the medial PFC of wild-type mice impairs recognition memory [160], which suggests that in the medial PFC, D3R acts via GSK3β signaling to play a role in the novel objects recognition memory.…”
Section: Da and 5-ht/akt/gsk3 Pathway Modulation And Its Behavioral Cmentioning
confidence: 97%
“…Hyper-dopaminergic mice display concomitant novelty-induced locomotor hyperactivity [157], which could be reduced by GSK3 inhibitors in the DAT lacking mice, and in amphetamine-treated normal mice [158,159]. Additionally, the inhibitory Ser9-phosphorylation of GSK3β is decreased in murine medial PFC after exposure of animals to novel objects, but the DAT knockdown mice exhibit no such decrease [160]. It has been found that the deletion of D3R in DAT knockdown mice restores novelty-induced GSK3β activation in the medial PFC.…”
Section: Da and 5-ht/akt/gsk3 Pathway Modulation And Its Behavioral Cmentioning
confidence: 99%
“…Beyond the well-known negative regulation of adenylyl cyclase, the D3R is involved in other, G-protein-independent intracellular signaling processes (e.g., GRK, ß-arrestin, GSK3, Akt, etc., see also in Section 5 ). Exposure to novelty such as in the novel object recognition task, is associated with the dephosphorylation of the two GSK3 kinase isoforms in the medial prefrontal cortex of mice [ 202 ]. GSK3 dephosphorylation is practically eliminated in DA transporter knockdown mice that also show deficits in novel object recognition performance, both of which can be rescued either by the genetic knockout of the D3R or the administration of the D3R antagonist FAUC365 [ 202 ].…”
Section: Site and Mechanism Of Action For D3r Antagonistsmentioning
confidence: 99%
“…Exposure to novelty such as in the novel object recognition task, is associated with the dephosphorylation of the two GSK3 kinase isoforms in the medial prefrontal cortex of mice [ 202 ]. GSK3 dephosphorylation is practically eliminated in DA transporter knockdown mice that also show deficits in novel object recognition performance, both of which can be rescued either by the genetic knockout of the D3R or the administration of the D3R antagonist FAUC365 [ 202 ]. Conversely, stimulation of D3Rs by the D2R/D3R agonist quinelorane causes a rapid and transient increase in the phosphorylation of GSK3, Akt and mTORC1 effectors in the nucleus accumbens and dorsal striatum in rats in vivo which can be prevented by the administration of the D3R antagonist S33084 [ 263 ].…”
Section: Site and Mechanism Of Action For D3r Antagonistsmentioning
confidence: 99%
“…Novel object recognition was found to depend on D2 DA receptor activity ( França et al, 2016 ). In DAT knockdown mice, the impairment of novel object recognition was observed ( Chang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%